2011
DOI: 10.1128/aac.00170-11
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Action and Limited Cross-Resistance of New Lipopeptide MX-2401

Abstract: MX-2401 is a semisynthetic calcium-dependent lipopeptide antibiotic (analogue of amphomycin) in preclinical development for the treatment of serious Gram-positive infections. In vitro and in vivo, MX-2401 demonstrates broad-spectrum bactericidal activity against Gram-positive organisms, including antibiotic-resistant strains. The objective of this study was to investigate the mechanism of action of MX-2401 and compare it with that of the lipopeptide daptomycin. The results indicated that although both daptomyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 45 publications
(75 reference statements)
2
62
0
Order By: Relevance
“…If the same concentrations were added separately to the calcein-loaded DOPC/DOPG liposomes, less than 10% leakage was observed even at 16 µg/mL daptomycin. Later, this same group, in collaboration with others, using essentially the same assay, reported only 7% calcein release from DOPC/PG liposomes at 32 µg/mL of daptomycin, 32 which seems more in line with the previously discussed results obtained with bacterial cells. 76 Using a coupled fluorescence assay that is based on the pH-sensitive indicator pyranine, 80 Zhang et al recently demonstrated that daptomycin can form pores in DMPC/DMPG (1:1) liposomes.…”
Section: Functional Size and Solute Specificity Of The Membrane Defectsupporting
confidence: 76%
See 3 more Smart Citations
“…If the same concentrations were added separately to the calcein-loaded DOPC/DOPG liposomes, less than 10% leakage was observed even at 16 µg/mL daptomycin. Later, this same group, in collaboration with others, using essentially the same assay, reported only 7% calcein release from DOPC/PG liposomes at 32 µg/mL of daptomycin, 32 which seems more in line with the previously discussed results obtained with bacterial cells. 76 Using a coupled fluorescence assay that is based on the pH-sensitive indicator pyranine, 80 Zhang et al recently demonstrated that daptomycin can form pores in DMPC/DMPG (1:1) liposomes.…”
Section: Functional Size and Solute Specificity Of The Membrane Defectsupporting
confidence: 76%
“…Using this assay, a fraction of the cells in a liquid culture of Staphylococcus epidermidis were found to be permeabilized after daptomycin treatment. 32 Such findings should be interpreted with caution, however. Propidium is very similar in structure to ethidium, which is widely used as a model substrate for bacterial efflux systems.…”
Section: Functional Size and Solute Specificity Of The Membrane Defectmentioning
confidence: 99%
See 2 more Smart Citations
“…At present, daptomycin is the only clinically used CDA, and its mode of action is the topic of ongoing investigation 6, 7, 8, 9. By comparison, the structurally similar CDAs laspartomycin C, friulimycin B, tsushimycin, and amphomycin have more clearly understood antibacterial mechanisms 10, 11, 12, 13, 14. It was recently reported that laspartomycin C forms a high‐affinity complex ( K d =7.3±3.8 n m ) with the bacterial cell wall precursor undecaprenyl phosphate (C 55 ‐P) and in doing so inhibits peptidoglycan biosynthesis, ultimately leading to cell death 14.…”
mentioning
confidence: 99%